2020
DOI: 10.1002/smll.202003425
|View full text |Cite
|
Sign up to set email alerts
|

Air Retention under Water by the Floating Fern Salvinia: The Crucial Role of a Trapped Air Layer as a Pneumatic Spring

Abstract: The ability of floating ferns Salvinia to keep a permanent layer of air under water is of great interest, e.g., for drag‐reducing ship coatings. The air‐retaining hairs are superhydrophobic, but have hydrophilic tips at their ends, pinning the air–water interface. Here, experimental and theoretical approaches are used to examine the contribution of this pinning effect for air‐layer stability under pressure changes. By applying the capillary adhesion technique, the adhesion forces of individual hairs to the wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 60 publications
0
42
0
Order By: Relevance
“…The hydrophilic tip fills the water-air interface and effectively maintains the stability of the air layer. Gandyra et al [138] called this structure "air-spring", which used the trapped air layer to form an elastic spring. When the air layer is impacted by pressure, the force that is subjected to the spring can be ejected from the bubble layer, which greatly improves the stability of the air layer [139] (Figure 11a-c).…”
Section: Physical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrophilic tip fills the water-air interface and effectively maintains the stability of the air layer. Gandyra et al [138] called this structure "air-spring", which used the trapped air layer to form an elastic spring. When the air layer is impacted by pressure, the force that is subjected to the spring can be ejected from the bubble layer, which greatly improves the stability of the air layer [139] (Figure 11a-c).…”
Section: Physical Methodsmentioning
confidence: 99%
“…b) We can calculate a model profile which shows 60% volume fraction of air in the corrugated upper zone.With these data, we can determine the effective air cushion thickness (air spring) to be 2.73 mm for this type of adult (half) leaf of S. molesta. Reproduced with permission [138]. Copyright 2020,Wiley-VCH.…”
mentioning
confidence: 99%
“…The excellent air‐retainability of Salvinia structures suggests they could be used long term in drag‐reduction applications. [ 34 ] In addition, several recent studies have confirmed that Salvinia structures reduced drag. For example, natural “eggbeater hairs” reduced drag by up to 30%, [ 77 ] and similar positive results have been obtained in qualitative studies on artificial Salvinia structures.…”
Section: Applications Of Artificial Salvinia Surfacesmentioning
confidence: 96%
“…4) Elastic buffer: the elasticity of the eggbeater structures provides a buffer against the slight deformation of the air–water interface, which helps reduce the interfacial disturbance. [ 34 ] Undercuts or simple inclinations are preconditions for elasticity.…”
Section: Air‐retention Mechanismmentioning
confidence: 99%
“…Therefore, the EU project AIRCOAT 1 aims at reducing hull friction to a minimum. In water ferns, the Salvinia effect of a micro-and nanostructured surface with hydrophobic and hydrophilic characteristics allows for air retention under water [1] and while the air spring effect contributes to the air layer stability [6]. Inspired by the Salvinia effect, the AIRCOAT project intends to develop a biomimetic passive air layer technology.…”
Section: Introductionmentioning
confidence: 99%